Functional Enterospheres Derived In Vitro from Human Pluripotent Stem Cells - Rohan R. Nadkarni; Soumeya Abed; Brian J. Cox; Sonam Bhatia; Jennifer T. Lau; Michael G. Surette; Jonathan S. Draper (Stem Cell Reports, 2017)
Intestinal organoids derived from human pluripotent stem cells (hPSCs) are valuable in vitro research models that enable simplified access to human gastrointestinal tissues. Here, we report the in vitro generation of enterospheres (hEnS) from hPSC-derived gastrointestinal epithelial precursors. hEnS are cystic spheroids with a simple uniform structure composed entirely of intestinal epithelium. hEnS express markers of mature brush border cells and share a transcriptome profile similar to that of more mature intestinal organoids. Modulation of signaling cues enables control of hEnS growth and differentiation, including long-term propagation. We show that hEnS can be exploited for functional studies: hEnS display an innate immune response when treated with enteric pathogens, and transgenic modification of hEnS with a fluorescence cell-cycle reporter enables hEnS-forming stem cell enrichment. Our work establishes hEnS as an accessible and tractable in vitro modeling system for studying human gastrointestinal biology.